Hemp Seed Priming via Different Agents to Alleviate Temperature Stress - Sibel Day; Burak Önol; Nilüfer Koçak (Journal of Agricultural Sciences)
Hemp (Cannabis sativa L.) seeds were treated with different priming agents (water, -0.8 MPa PEG 6000, 50 mMol thiamine and 10 mMol mannitol) and subjected to different temperatures (10, 15, 20, 25 and 30 °C). The impacts of low and high temperature on germination and initial growth, along with optimal conditions, were evaluated with priming agents. Results revealed that seed treatment accelerated mean germination time and increased emergence percentage at lower temperatures. The minimum mean germination times of 1.38 and 1.39 days were obtained at 20 °C with hydro priming and mannitol priming. The maximum germination percentages of 89.5 and 90% were observed with mannitol and hydro priming at 20 °C. Retarded seedling emergence was noted at 10 °C. Minimum emergence percentage at 10 °C was 46% in control samples. Seed pre-treatments also promoted shoot length at all temperatures. However, root length promoting effects of seed treatments were more evident at 10, 15 and 20 °C. The minimum root length was 3.04 cm in controls at 30 °C. Seedling fresh and dry weight reached maximum values at 20 °C with water, thiamine and mannitol treatments. Chlorophyll and leaf proline content reached their highest values at 20, 25 and 30 °C. Overcoming temperature stress and promoting germination is important for hemp development. It was concluded that hemp seeds primed with water, thiamine, and mannitol had the highest biomass values for low, optimum, and high temperatures in this study. This indicates that these seed treatments are suitable for hemp plants that could experience low or high temperatures during germination and early growth stages.